PENGEMBANGAN MADRASAH PERSPEKTIF BLUE OCEAN STRATEGY MTs ALISLAM JORESAN PONOROGO - Rofiqi, Mufid Ahsan; Kolis, Nur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2020)
Abstrak: One of the institutions is MTs Al-Islam Joresan which has experienced an increase in interest over a period of 4 years, when several institutions are competing to slam prices, is considered successful in carrying out its strategy.The researcher wants to know the MTs Al Islam strategy when it is read qualitatively descriptive with a blue ocean strategy (BOS) perspective. First, what is the formulation and implementation of BOS? Second, what is the focus of the institution if seen from the principles of ERRC (eliminate, reduce, raise, create)? Based on the data collected and analyzed, it can be seen that the first MTs Al-Islam Institutions have carried out the strategy formulation stage and implemented it according to the perspective of the Blue Ocean Strategy. Second MTs Al-Islam institutions have carried out the principles of Eliminate, reduce, and raise, and have not implemented the principle of create. Abstrak: Salah satu lembaga MTs Al-Islam Joresan yang mengalami kenaikan peminat selama kurun waktu 4 tahun, disaat beberapa lembaga berlomba membanting harga, dianggap sukses menjalankan strateginya. Penelitian kualitatif ini ingin menganalisis strategi MTs Al Islam dalam mengembangkan madrasah dengan perspektif blue ocean strategy (BOS), yang meliputi syarat perumusan dan fokusya dalam perpektif BOS. Hasil penelitian menunjukkan bahwa lembaga MTs Al-Islam telah memenuhi syarat Blue Ocean strategy; yaitu: fokus pada kurva lembaganya, divergensi( gerak menjauh dari persaingan), serta memiliki motto yang memikat (Merawat Tradisi Dan Merespon Modernisai). Lembaga MTs Al-Islam telah melakukan tahapan perumusan strategy serta meng-implementasikan nya menurut perspektf Blue Ocean Strategy. lembaga MTs Al-Islam telah melakukan prinsip Eliminate, reduce, dan raise, serta belum menjalankan prinsip create.